Hubungan Antara Tekanan Darah Pre Hemodialisis Dan Lama Menjalani Hemodialisis Dengan Penambahan Berat Badan Interdialitik Di Ruang Hemodialisis Rs. Moh. Hoesin Palembang - Rumentalia Sulistini; Indah Permata Sari; Natsir A Hamid (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2014)
Chronic Renal Failure (CRF) now has become a serious problem for people’s health in the world. CRF often causes various complications, one of them is cardiovascular. Prevalence of cognitive impairment in chronic kidney diseases accurs about 37% after two years hemodialisis treatment. Interdialytic Weight Gain (IDWG) is an indicator of fluid over a period of interdialytic input can influence health status in patients undergoing hemodialysis. The occurrence of interdialysis weight gain will be raised a variety of issues for patients. The purpose of this study is to determine the correlation between blood pressure pre hemodialysis and length of hemodialysis toward interdialytic weight gain in RSUP dr. Mohammad Hoesin Palembang 2013. The study occurred by using the method of analytic survey with crosssectional approachment to the acquisition of sample using purposive sampling totaling 43 peoples, technique determines the amount of samples using the inclusion criteria, as for research using questionnaires blood pressure, length of hemodialysis and interdialytic weight gain. Data analysis occurred with the Regression Correlation with value = 0,05. The results showed there was no significant correlation between blood pressure (systole and diastole) pre hemodialysis and interdialitic weight gain (p > 0,05) with a standard deviation of 23,754 mmHg in blood pressure of systole and 9,359 mmHg in diastole blood pressure. As for the length of hemodialysis have a significant correlation with interdialytic weight gain (p < 0,05) with a standard deviation of 16,539 months. Recommendation results of this study areexpected to nurse to provide health education on diet for people with CRF as a whole so that the client can choose the food and drink can be consumed as well as the quantities that allowed so there is no complication.